Evaluation of the TERKONTROL Application to Improve Control Compliance of Non-Communicable Diseases and Elderly Patients: Evaluasi Aplikasi TERKONTROL untuk Meningkatkan Kepatuhan Kontrol Pasien PTM dan Lansia - Alwan Wijaya; Artha; Nining Wahyuni Yuriasti; Eni Yuriasti; Dodi Wijaya; Rondhianto (Journal of Community Empowerment for Multidisciplinary (JCEMTY), 2025)
Low adherence of patients with Non-Communicable Diseases (NCDs) and the elderly to scheduled follow-up visits remains a major challenge in primary healthcare services. This issue contributes to delayed detection of complications and reduced effectiveness in managing chronic conditions. This community service program aimed to evaluate the effectiveness of the TERKONTROL application—an automated WhatsApp-based reminder system designed to improve the regularity of patient follow-up visits. The program was implemented at Dasan Agung Public Health Center using a Participatory Action Research (PAR) approach, actively involving program officers, academic facilitators, and patients. The desktop-based application features patient data input, visit scheduling, a monitoring dashboard, and an automated reminder system. Implementation results showed that out of 16 patients who received reminder messages, 13 attended their scheduled visits, achieving a compliance rate of 81.3%. Evaluation revealed positive perceptions from both patients and healthcare staff regarding the application's usability and usefulness. These findings suggest that simple digital innovations such as TERKONTROL (Tertib Kontrol dan Respon Lanjut Pasien PTM & Lansia) can serve as effective tools for real-time patient monitoring, program reporting enhancement, and improved communication in primary healthcare settings.